Investigation of Colorado front range winter storms using a nonhydrostatic mesoscale numerical model designed for operational use - Snook, John S., author (Colorado State University. Libraries, 1993)
State-of-the-art data sources such as Doppler radar, automated surface observations, wind profiler, digital satellite, and aircraft reports are for the first time providing the capability to generate real-time, operational three-dimensional gridded data sets with sufficient spatial and temporal resolutions to diagnose the structure and evolution of mesoscale systems. A prototype data assimilation system of this type, called the Local Analysis and Prediction System (LAPS), is being developed at the National Oceanic and Atmospheric System's Forecast Systems Laboratory (FSL). The investigation utilizes the three-dimensional LAPS analyses for initialization of the full physics, nonhydrostatic Regional Atmospheric Modeling System (RAMS) model developed at the Colorado State University to create a system capable of generating operational mesoscale predictions. The LAPS/RAMS system structured for operational use can add significant value to existing operational model output and can provide an improved scientific understanding of mesoscale weather events. The results a.re presented through two case study analyses, the 7 January 1992 Colorado Front Range blizzard and the 8-9 March 1992 eastern Colorado snowstorm. Both cases a.re ideal for this investigation due to the significant mesoscale variation observed in the precipitation and flow structure. The case study results demonstrate the ability to successfully detect and predict mesoscale features using a mesoscale numerical model initialized with high resolution (10 km horizontal grid interval), non homogeneous data. Conceptual models of the two snowstorms are developed by utilizing the RAMS model output in combination with observations and other larger domain model simulations. The strong influence of the Colorado topography on the resultant flow is suggested by the generation of a lee vortex that frequently develops east of the Front Range and south of the Cheyenne Ridge in stable, northwest synoptic flow. The lee vortex, often called the "Longmont anticyclone", exhibits surface flow characteristics that are similar to results from low Froude number flow around an isolated obstacle. A series of numerical experiments using RAMS with idealized topography and horizontally homogeneous initial conditions are presented to investigate typical low Froude number flow characteristics in the vicinity of barriers representative of the Colorado topography. The results are compared to the findings of previous investigations and to the case study observations and numerical predictions. The findings suggest that the Colorado orography significantly altered the low-level flow in both case studies resulting in mesoscale variation of observed precipitation. Improved representation of the topography by the model led to the majority of the forecast improvement.
Fall 1993.
Also issued as author's sdissertation (Ph.D.) -- Colorado State University, 1993.
Keywords: Winter storms -- Colorado -- Mathematical models; Numerical weather forecasting -- Colorado; Mesometeorology -- Colorado; Winter storms -- Front Range (Colo. and Wyo.)